(3JMQjQ cJGH TGhOhSjhS aj GdCjGe hGddjGdis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3KGhOhSjhSs
(3ChdgG (B:s
(3GdTeS eJMQcg eYJOdg VO MQcg Gdcd Ydi efWbI GdHQhL s
(3BNQgG (B:s
(3hcGfJ ZjQ ebOQg GdMce KGHJ hPdc eG CQOfGg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B126 - (3U(B132s
(3jMJhi Ydi QShe gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B512 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3453(10)) s
Keywords: (3Gdadcs